DETERMINATION OF THE SLIDING STATE OF THE SOILS OF THE SHYMBULAK SLOPE WITH THE DEVELOPMENT OF THE CRITERION OF FAILURE - Z M. Abdiakhmetova; A. R. Baimakhan; R. B. Baimakhan (Вестник КазНУ. Серия математика, механика, информатика, 2021)
On the basis of the known criterion for the destruction of Coulomb Mor applied to soils of isotropic structure, developed the general criteria for the destruction of stratified, anisotropic, inclined layer of soils. New expressions were obtained to determine the parameters of the mechanics of disruption allowing not only the direction of disruption, but also the possible distribution of dislocations along the layers of soil and perpendicular. Applying the proposed criterion, the problem of determining the stressful condition of the soils of the dangerous rock slope of the slope, and on the joints of soils of different geological structure, such as eluvium and delta. The results of the analysis are presented in the form of tables, diagrams and graphs. Deductions are made on the reliability of the proposed approach to the solution of the problem on the determination of the precondition of the soil of mountain slopes. The first part of the work describes the different categories of communication conditions. The second section gives various examples of the construction of individual elastic curved joints and their connections, supplemented by certain connection conditions of the limit problem. The result is a numerical calculation of the natural frequency of free oscillations of the joints of elastic bent joints.